2009
DOI: 10.1016/j.jvs.2009.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of carotid artery stenosis after radiotherapy for head and neck cancers

Abstract: In head and neck cancer, the high post-treatment incidence of radiation-induced CAS indicates the importance of regular examination of the carotid duplex and early antiplatelet prophylaxis. Different age groups may require different irradiation strategies to prevent radiation-induced CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 17 publications
4
95
0
1
Order By: Relevance
“…A possible explanation for the higher risk may be the differences in radiation doses, which were confirmed by Chang et al [18]. In conclusion, RT in addition to other traditional risk factors has a combined effect on the progression of postradiation atherosclerosis.…”
Section: Risk Factorsmentioning
confidence: 65%
See 1 more Smart Citation
“…A possible explanation for the higher risk may be the differences in radiation doses, which were confirmed by Chang et al [18]. In conclusion, RT in addition to other traditional risk factors has a combined effect on the progression of postradiation atherosclerosis.…”
Section: Risk Factorsmentioning
confidence: 65%
“…Lam et al [2] found that age and irradiation were important factors in the development of carotid stenosis. Chang et al [18] showed a positive correlation between the total plaque score, which is an index of atherosclerosis, RT use, RT dose, length of time after RT, hyperlipidemia, and age. The study of Cheng et al [3] revealed that severe post-RT carotid stenosis was associated with age, smoking, heart disease, no prior oncological surgery, cerebrovascular symptoms and interval from RT.…”
Section: Risk Factorsmentioning
confidence: 99%
“…42 Whereas the earlier study is 1 of the largest of its kind to date, XRT protocol data are missing, sonographic interpretation was not blinded, and patients were only "asked" about previous possible CVEs. Despite this, a similarly sized study by Chang et al (290 patients) 34 lends weight to the results. Head and neck cancer patients were consecutively recruited (198 after XRT, 92 before XRT).…”
Section: Head and Neck Xrtmentioning
confidence: 88%
“…Après irradiation du cou, le taux de sténose carotidienne supérieure à 50 % est de 20 %. L'âge inférieur à 50 ans est le principal facteur pronostique défavorable [53]. Un contrôle vasculaire est justifié chez ces patients.…”
Section: Autre Toxicité Radio-induiteunclassified